Pengaruh Beauty Vlogger, Brand Image, Harga dan Label Halal Terhadap Keputusan Pembelian Produk Kosmetik Make Over Pada Toko Kosmetik Arum Beauty Shop Lawang - Widya Rizqi Kusuma Wardhani; Rois Arifin; Andi Normaladewi (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to identify and analyze beauty vloggers, brand image, prices and halal labels that simultaneously and partially influence the purchase decision of Make Over cosmetic products. This research is located in the Arum Beauty Shop Lawang cosmetic shop. This type of research uses descriptive quantitative. The data used is primary data, obtained from interviews and questionnaires filled out directly by respondents who are consumers of the Arum Beauty Shop cosmetic shop. The sample used is 100 respondents.Data analysis was carried out using the SPSS 26 program. The sampling technique used was purposive sampling. The data analysis technique in this study used multiple linear regression. The results of this study indicate that beauty vlogger, brand image, price and halal label have a significant positive effect on purchasing decisions for Make Over cosmetic products. Keywords: Beauty Vlogger, Brand image, Price, Halal Label.